Design of a control system of autonomous trailer - Medina Medina , Wilder (2022)
The present work defines a control design, which consists of integrating two techniques: linear LQR and a neuro-diffuse network, in such a way that this hybrid system provides a wide working range for the trailer to follow any trajectory in advance and recoil directions simulating the real conditions of human driving. It is also proposed the monitoring of any trajectory designing a general method to calculate the desired values of the system states, in such a way that, by simply defining a mathematical function of the route to follow, the values for the control of the trailer type robot are known. Favourable results of the system were achieved and applied in a controlled environment.